Air Pollution and Lung Capacity of People Living around the Cement Industry - Jayadipraja, Erwin Azizi; Daud, Anwar; Assegaf, Alimuddin Hamzah; -, Maming (YCAB Publisher & IAKMI SULTRA, 2016)
Backgrounds: A cement industry is one of anthropogenic sources of air pollution. In polluting the air, the industry creates some dust particles, nitrogen oxide (NO2), sulfur oxide (SO2), and carbon monoxide (CO).Research Purpose: The research aims at finding out the ambient air quality around a cement industry and relating it with the lung capacity of people living around the area.Methodology: This research uses cross sectional studies by measuring the ambient air quality in the morning, noon, and evening in four different settlements within 3 km from the cement industry. The measurement is then correlated with the FEV1 and FVC of lung capacity of people living around the area.Result: Of all four locations, three have ambient air quality (PM2.5 = 109.47 µg/Nm3, TSP = 454.7 µg/Nm3) that surpass the quality standard (PM2.5 = 65 µg/Nm3, TSP = 230 µg/Nm3). Of 241 respondents, the average level of FVC and FEV1 is respectively 1.9352 liter (SD: 0.45578) and 1.7486 liter (SD: 0.43874). Furthermore, the level of PM2.5 in the morning and at noon is respectively p=0.009 and p=0.003; the level of TSP in the morning and at noon is respectively p=0.003 and p=0.01; the level of NO2 in the morning is p=0.006; the level of SO2 in the morning, at noon and in the evening is respectively p=0.000, p=0.022, and p=0.000; and the level of CO in the morning, at noon and in the evening is respectively p=0.003, p=0.015, and p=0.024. Those levels are associated with the level of respondents' FEV1. Moreover, the level of TSP in the morning is p=0.024; the level of SO2 in the morning and in the evening is p=0.007. These levels relate to the level of respondents' FVC.Keywords: FVC, FEV1, CO, NO2, SO2, TSP, PM2.5, cement industry.